Analisis Upaya Hukum Bagi Peserta Magang MBKM Dalam Menuntut Hak-Hak Berdasarkan Sistem Hukum Ketenagakerjaan Di Indonesia - Jemadur, Yohanes Brilian; Wahjoeono, Dipo (Jurnal Restorative Justice, 2024)
The Merdeka Campus Learning Internship Program (MBKM) provides students with the opportunity to gain valuable work experience relevant to their fields of study. However, interns often face challenges in asserting their rights, such as fair wages, appropriate working hours, and adequate legal protections. This study aims to analyze the legal efforts that MBKM interns can undertake to claim their rights based on the labor law system in Indonesia. The type of research used is normative legal research with a statute approach and a conceptual approach. The results show that although interns have certain rights, awareness of these rights remains low. Many interns are unaware that they are entitled to the same legal protections as other workers, resulting in frequent unfair treatment. Additionally, there are shortcomings in the regulations governing the protection of interns, which often leaves them vulnerable to exploitation by companies. Recommendations are made to enhance legal protection for interns, including the need for socialization regarding their rights to students and industry stakeholders. Educational institutions are also expected to play an active role in providing clear information about the rights held by interns. Furthermore, it is important to involve companies in creating a fairer and more transparent internship environment. Thus, it is hoped that interns can be more proactive in asserting their rights and gaining beneficial experience during their internship, contributing to their professional development in the future. This research is expected to serve as a reference for improving internship policies and practices in Indonesia.